Relationship Between the Lipid Accumulation Product Index and Arterial Stiffness in the Chinese Population With Hypertension: A Report From the China H-Type Hypertension Registry Study - Shi, Yumeng; Hu, Lihua; Li, Minghui; Zhou, Wei; Wang, Tao; Zhu, Lingjuan; Bao, Huihui; Li, Ping; Cheng, Xiaoshu (Frontiers in Cardiovascular Medicine, 2022)
Background Lipid accumulation product (LAP) index, as a new index to predict cardiovascular disease (CVD), has attracted the attention of many researchers. The relation of the LAP index with brachial-ankle pulse wave velocity (baPWV) has been evaluated in several previous studies and yielded inconsistent results. This study aimed to investigate the association between the LAP index and arterial stiffness in the Chinese population with hypertension. Methods We conducted a cross-sectional analysis in 4,926 Chinese population with hypertension (aged 64.42 ± 9.44 years). The LAP index was developed from population-based frequency plots of adult waist circumferences and circulating triglyceride concentrations according to men and women. Arterial stiffness was determined by measuring baPWV. Results The multivariate linear regression analyses showed that the LAP index was independently and positively associated with baPWV [beta coefficients (β), 24.10 cm/s; 95% CI: 5.72, 42.49 cm/s]. Consistently, the multivariate logistic regression analyses showed a positive association between the LAP index risk of elevated baPWV (>75th percentile) [odds ratio (OR), 1.19; 95% CI 1.01, 1.41]. A restricted cubic spline showed that a significant linear association existed between the LAP index and baPWV. In different subgroups of diastolic blood pressure (DBP), there is interaction between the LAP index and baPWV (DBP <90, 90–99, ≥100 mm Hg; p-interaction = 0.006). Conclusion LAP is significantly positively associated with baPWV and elevated baPWV in Chinese hypertensive adults and especially among participants with DBP ≤ 99 mm Hg.